If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(t + 1) + -13 = 14 Reorder the terms: 9(1 + t) + -13 = 14 (1 * 9 + t * 9) + -13 = 14 (9 + 9t) + -13 = 14 Reorder the terms: 9 + -13 + 9t = 14 Combine like terms: 9 + -13 = -4 -4 + 9t = 14 Solving -4 + 9t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9t = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 9t = 14 + 4 9t = 14 + 4 Combine like terms: 14 + 4 = 18 9t = 18 Divide each side by '9'. t = 2 Simplifying t = 2
| (X-4)+3(x+5)=51 | | 4(q-13)-6=2 | | -5v-17=9(v-5) | | p*204=342 | | -3/5*-3/5*-3/5*-3/5*-3/5 | | 10-d=4 | | 12b+3b-6b-8b-1=15 | | 7log(3x)+3log(5x)=5 | | 7h-35=95 | | 10s-12s+3s=-6 | | -20a+12a+11a=9 | | 10=3(y+2)+1 | | 10c-7c=18 | | 4z^10+6=1 | | 3(k-7)+2=8 | | 4z+5z=12+42 | | 19z+47=185 | | 2+3z=11 | | -4y+3b+8y+8b= | | 17x+17=4(4x+4) | | P=2a+2l | | 2w+4=6 | | -18k-2k+-8=8 | | x^2-2x-3/x^2-81 | | 5g+4=94 | | 4=16-2b | | 3t+2tb= | | 4*-1-3= | | -6(z+2)+3(4z-3)=5(z-3)+12 | | 6xy(-3)+12(-3x+2xy)-17= | | 98=7(r+3) | | 6=y+12 |